PENGARUH APLIKASI TIKTOK TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB DI KELAS IV SD IT GENERASI MADANI SAMPALI - Dewi Ani Siregar; Sultoni Trikusuma; Dewi Sundari (STKIP Subang, 2026)
This research is motivated by the low level of students’ interest in learning Arabic, which is often perceived as difficult and less engaging. Therefore, this study aims to: (1) identify how the TikTok application is used in Arabic language learning for fourth-grade students at SD IT Generasi Madani Sampali; (2) determine the level of students’ interest in learning Arabic; and (3) examine whether the use of the TikTok application influences students’ interest in learning Arabic in grade IV at SD IT Generasi Madani Sampali.This study employed a quantitative research design. The data sources consisted of primary and secondary data. The population of this study was 30 students, and a saturated sampling technique was applied. Data were collected through questionnaires and documentation. The data analysis techniques included: (1) descriptive statistical analysis; (2) instrument testing, consisting of validity and reliability tests; (3) prerequisite tests, namely normality and linearity tests; and (4) hypothesis testing using simple linear regression, partial tests (t-test), and the coefficient of determination.The results showed that the partial t-test produced a significance value of 0.00, which is less than 0.05. This indicates that H₀ is rejected and Hₐ is accepted, meaning that the use of the TikTok application has a significant effect on students’ interest in learning Arabic for fourth-grade students at SD IT Generasi Madani Sampali. The magnitude of the influence of the TikTok application on students’ interest in learning Arabic was 50%, while the remaining 50% was influenced by other factors not examined in this study.